Checks and Balances in Neuromodulation - Harris-Warrick, Ronald M.; Johnson, Bruce R. (Frontiers in Behavioral Neuroscience, 2010)
Neuromodulators such as monoamines and peptides play important roles in activating and reconfiguring neural networks to allow behavioral flexibility. While the net effects of a neuromodulator change the network in a particular direction, careful studies of modulatory effects reveal multiple cases where a neuromodulator will activate functionally opposing mechanisms on a single neuron or synapse. This review gives examples of such opposing actions, focusing on the lobster pyloric network, and discusses their possible functional significance. One important action of opposing modulatory actions may be to stabilize the modulated state of the network, and to prevent it from being overmodulated and becoming non-functional.